Job stress characteristics and its consequences on the employees in institutions of higher learning : co-worker’s social support as the moderator - Chin, Melissa Yu Fei (Universiti Malaysia Sarawak (UNIMAS), 2014)
Stress occurs be it at home, school or the workplace. In the context of organization, stress affects how the worker performs and feels on and off the job. If stress is not handled properly it will further affect the worker mentally and physically. Several past studies have shown that social support can help to moderate the impacts of job stress on an individual. This research examines the impacts of job stress characteristics on the workforce on work family conflict and employee’s health. A sample of 203 from both academic and non-academic staff were obtained from several higher learning institutions in Kuching. By using Pearson Correlation Analysis and Hierarchical regression analysis, results shows that (1) job stress characteristics (role ambiguity, role conflict and role overload) affects work-family conflict and employee’s health, and (2) co-worker’s social support does have moderating effects on the impacts of job stress characteristics on work-family conflict and employee’s health. Implications of the findings for research and interventions are discussed. The results from this study supported most research literatures in Malaysian organizational settings. Therefore, organizations in Malaysia may use this as a guideline to create a more balanced and healthy workforce.